RANCANG BANGUN TURBIN ANGIN SAVONIUS 200 WATT - Rudianto, Daniel; Ahmadi, Nurfi (Sekolah Tinggi Teknologi Adisutjipto, 2016)
This study aimed to establish the type of Savonius wind turbines that capable of generating electric power of 200 Watts. This objective relates to Bantul District Government program which plans to build wind turbin generating electrical power (Pembangkit Listrik Tenaga Bayu, PLTB) 200 Watt as a backup power source for powering cooling fish caught by fishermen in the southern coast. Savonius Turbine chosen with consideration that it has simple construction so that the cost is not expensive, not depending on the direction of the wind, and is suitable for small power plants.Design of Savonius turbine blade has been completed, the turbine blade height 168 cm and a diameter of 55 cm. Blade turbine mounted on an arm along 55 cm from the turbine shaft and separate 120º. The turbine is supported by a 3-foot-tall turbines framework 2,5 m iron box 4 cm x 4 cm. The test simulated to determine the turbine rotation has been performed at varying wind speeds, i.e. 2 m /s, 4 m /s and 6 m /s.Based on test results, the turbine is capable of rotating an average of 54,2 rpm at a wind speed of 2 m /s; 86,8 rpm at a wind speed of 4 m /s; and 124,2 rpm at a wind speed of 6 m /s. These test results indicate that the Savonius turbines can be used to drive a generator producing the need of electrical energy